2016
DOI: 10.1037/a0039202
|View full text |Cite
|
Sign up to set email alerts
|

Outcome expectancy as a process indicator in comprehensive worksite stress management interventions.

Abstract: This study investigates the relationship between outcome expectancy for an individual stress management course and the total perceived impact of a comprehensive stress management intervention (SMI). It is based on data from three different measurement points from a longitudinal SMI in Switzerland. Individual and organizational outcome expectancies for stress management courses were captured with two newly developed items (SMI outcome expectancy) immediately after course completion. Perceived individual and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 61 publications
(119 reference statements)
0
22
0
Order By: Relevance
“…Another study showed that employees' baseline readiness for implementing a new information system was linked to their satisfaction with the new system after a month of using it (Jones, Jimmieson, & Griffiths, 2005). Furthermore, a recent study evaluating the influence of outcome expectancy on the outcomes of a stress management course found that both individual and organizational outcome expectancy predicted the perceived impact of the course (Fridrich, Jenny, & Bauer, 2016). However, existing studies have mainly focused on evaluating readiness on a general level, most often readiness for the overall content of the intervention.…”
Section: Mental Modelsmentioning
confidence: 99%
“…Another study showed that employees' baseline readiness for implementing a new information system was linked to their satisfaction with the new system after a month of using it (Jones, Jimmieson, & Griffiths, 2005). Furthermore, a recent study evaluating the influence of outcome expectancy on the outcomes of a stress management course found that both individual and organizational outcome expectancy predicted the perceived impact of the course (Fridrich, Jenny, & Bauer, 2016). However, existing studies have mainly focused on evaluating readiness on a general level, most often readiness for the overall content of the intervention.…”
Section: Mental Modelsmentioning
confidence: 99%
“…"; "Do you think the workshop will have a positive impact on your team?") (Fridrich et al, 2016). The items were rated by the workshop participants on a 7-point Likert scale from 1 = no, not at all to 7 = yes, very much.…”
Section: Outcome Expectancymentioning
confidence: 99%
“…Bunce (1997) argued that it is likely that such expectations moderate the effectiveness of an intervention. Fridrich et al (2016) found that the outcome expectancy of a stress-management workshop is able to partly predict the perceived individual and organizational impact of the entire stress-management intervention in a 2-year follow-up. Similarly, both Füllemann et al (2016) and Lehmann et al (2019) showed that outcome expectancy -measured during workshops of an organizational health intervention -was related to follow-up perceptions of impact.…”
Section: Introductionmentioning
confidence: 96%
“…Jenny et al 2015;Fridrich et al 2016b). To introduce the scale, employees were shortly reminded of the activities of the intervention and then asked to rate the overall perceived impact of the entire intervention in their nursing ward.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Outcome expectancies were measured using three items that captured whether the workshop participants expected the workshops including developed action plans to trigger positive changes in their personal working conditions, their team and the work processes within the team (Fridrich et al 2016b). A sample item is, "Do you think the workshop will have a positive effect on your work?"…”
Section: Process Measuresmentioning
confidence: 99%